DAMPAK LIKUIDITAS DAN PROFITABILITAS TERHADAP HARGA SAHAM PADA OTOMOTIF YANG TERDAFTAR DI BURSA EFEK INDONESIA - FARIDA SAGALA (LP2MTBM MAKARIOZ, 2021)
The purpose of this study is to determine the impact of liquidity and profitability on the share price on automotive listed on theIndonesia stock exchange. The results stated that the Current Ratio (X1) partially positively and significantly affects theShare Price of automotive subsector companies listed on the Indonesia Stock Exchange for the period 2012-2016. Thisresult was seen from the regression capacity of 236,347 and the significance level of 0.002 < 0.05. Debt to Equity Ratio (X2)partially positively but insignificantly affects the Share Price of automotive subsector companies listed on the Indonesia StockExchange for the period 2012-2016. This result is seen from the regression coefficient of 20,450 and the sigifikansi rate of0.318 > 0.05. Net Profit Margin (X3) partially positively and significantly affects the Share Price of automotive subsectorcompanies listed on the Indonesia Stock Exchange for the period 2012-2016. This can be seen from the regressioncoefficient of 20,189 and the significance level of 0.047< 0.05.